MENINGKATKAN KETERAMPILAN SISWA PADA PENJUMLAHAN BILANGAN BULAT DENGAN MEDIA LIDI PADA KELAS IV SEMESTER GENAP SDN PEMBINA TATABA TAHUN PELAJARAN 2019/2020: SDN PEMBINA TATABA - SABARIA BAHALIA (Mitra Pendidikan, 2022)
This study aims to make students able to improve the skills of using stick media in solving problems related to the addition of integers. The type of research used by the author in this study is Classroom Action Research (CAR). Classroom Action Research is a variety of classroom-context learning research carried out by teachers to solve learning problems faced by teachers, improve the quality and learning outcomes and try new things in learning for the sake of improving the quality and learning outcomes. CAR has its own characteristics that distinguish it from other research, including the problems raised are problems faced by teachers in the classroom and certain things to improve the teaching and learning process in the classroom (Suharsimi Arikunto.2007) This research was conducted in class IV of Pembina Tataba Elementary School, Buko District, Banggai Islands Regency. The research subjects were fourth grade students at Pembina Tataba Elementary School, Buko District, Banggai Islands Regency with a total of 17 students with a distribution of 8 male students and 9 female students. for two months from January 3 to February 29, 2020. The subjects and subject matter that will be used in this research are mathematics subjects with the subject matter of adding integers in class IV even semester The data collection technique used in this classroom action research is through 1). Learning Outcomes Test, and 2) Observation Sheet. The data obtained from the observation and assessment of learning outcomes are classified based on student groups which are then analyzed by qualitative data analysis techniques. Based on the results of the implementation of classroom action research, it can be concluded 1). Learning by using sticks media in pairs, using colored sticks media in pairs and using individually colored sticks media can improve student achievement in the addition of integers. 2). Learning using stick media can increase student activity, be more passionate, have no fear, be active, happy, and creative. 3). Providing opportunities for researchers to be able to play roles in order to provide direct experience for students to motivate their learning